REVEA: Towards a New Generation of Virtual Training Tools for Elite Sport - Kulpa, Richard (Réflexions Sport, 2024)
The REVEA project aims to integrate virtual reality into the core training of elite athletes to address specific performance challenges in boxing, athletics and gymnastics, while reducing the risk of injury. For boxers, a virtual opponent accurately simulates attacks, allowing them to develop anticipation and counter-attacking skills without the physical impact of real punches. In the 4 × 100m relay in athletics, a virtual simulator immerses relay runners in an accurate replica of the track, allowing them to fine-tune their start timing and optimise baton exchanges, while avoiding the physical strain of repeated starts and sprints. For gymnasts, virtual reality provides an immersive mirror in which they can observe and adjust their movements in a safe environment, facilitating the mastery of complex technical skills. This project, the result of close collaboration between elite coaches and leading researchers in their fields, also includes a detailed analysis of the athletes’ acceptance and engagement with this new virtual reality technology. Through its innovative nature and forward-looking approach, REVEA aims to become an important complementary axis to traditional training, ready to evolve over the course of Olympic cycles to better meet the demands of high performance.